2016
DOI: 10.1177/1358863x16629727
|View full text |Cite
|
Sign up to set email alerts
|

Volumetry and biomechanical parameters detected by 3D and 2D ultrasound in patients with and without an abdominal aortic aneurysm

Abstract: The objective was to demonstrate the ability of ultrasound (US) with 3D properties to evaluate volumetry and biomechanical parameters of the aorta in patients with and without abdominal aortic aneurysm (AAA). Thirty-one patients with normal aortas (group 1), 46 patients with AAA measuring 3.0-5.5 cm (group 2) and 31 patients with AAA ⩾ 5.5 cm (group 3) underwent a 2D/3D-US examination of the infra-renal aorta, and the images were post-processed prior to being analyzed. In the maximum diameter, the global circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
(47 reference statements)
3
15
2
Order By: Relevance
“…They found that maximum circumferential strain was lower in the aneurysm group compared to controls. Furthermore, maximum global rotation was the highest in the control group and lowest in AAAs ≥5.5 cm 45 . A study by Taniguchi et al 46 showed that aortic strain rate was lower, but also had greater heterogeneity in patients with abdominal aortic aneurysm than in those with normal aortas.…”
Section: Ultrasound Assessment Of Aortic Biomechanicsmentioning
confidence: 91%
See 1 more Smart Citation
“…They found that maximum circumferential strain was lower in the aneurysm group compared to controls. Furthermore, maximum global rotation was the highest in the control group and lowest in AAAs ≥5.5 cm 45 . A study by Taniguchi et al 46 showed that aortic strain rate was lower, but also had greater heterogeneity in patients with abdominal aortic aneurysm than in those with normal aortas.…”
Section: Ultrasound Assessment Of Aortic Biomechanicsmentioning
confidence: 91%
“…The group found that the ascending aortas of DPAA group with wider aortas (>45 mm) had reduced strain, reduced distensibility, and increased stiffness compared to controls. Batagini et al 45 used STE to assess maximum circumferential strain, global rotation of the aorta in patients with normal aortas, and abdominal aortic aneurysms. They found that maximum circumferential strain was lower in the aneurysm group compared to controls.…”
Section: Ultrasound Assessment Of Aortic Biomechanicsmentioning
confidence: 99%
“…Recently, even ultrasonography has been used for biomechanical evaluation of AAA. 35 Lastly, since the role of WSS has not been elucidated in AAA pathogenesis, CFD should be assessed in larger cohorts and in conjunction with FEA. And because FSI uses haemodynamics in its calculation of PWS, a comparison with FEA should be made to see if this inclusion actually refines the biomechanical evaluation.…”
Section: Future Perspectivementioning
confidence: 99%
“…Ultrasound, abdominal aortic aneurysm.An transverse (a) and oblique (b) images are presented in gray-scale scanning[18].…”
mentioning
confidence: 99%